Synthesis, Characterization and Antifungal Activity of Some Substituted 4-thiazolidinone Derivatives - Hamdan Salameh Al-Ebaisat; Taher Sharif Ababne; Tareq Mousa Al Shboul; Taghreed M. Jazzazi (The Journal of Pure and Applied Chemistry Research, 2016)
A series of 4-thiazolidinone derivatives was prepared including 2- (4-phenyl)-3-(4-hydroxyphenyl)thiazolidinone-4-one (1), 2-(4-bromophenyl)-3-(4-hydroxy phenyl) thiazolidinone-4-one (2), 2-(4-chlorophenyl)-3-(4-hydroxyphenyl) thiazolidinone-4-one (3), 2-(4-methylphenyl)-3-(4-hydroxyphenyl) thiazolidinone-4-one (4),  2-(4-metoxyphenyl)-3-(4-hydroxyphenyl) thiazolidinone-4-one (5), 2-(4-nitrophenyl)-3-(4-hydroxyphenyl) thiazolidinone-4-one (6), 2,3-bis(4-hydroxyphenyl) thiazolidinone-4-one (7) and 2-(4-ethyl phenyl)-3-(4-hydroxyphenyl) thiazolidinone-4-one (8).   The chemical structures of prepared compounds have been characterized by Mass, IR, 1H-NMR, and elemental analyses. The biological activity of these compounds as fungicides was tested against three commercially known fungicides (C. albicans, patient isolate C. glabrata and C. krusei). The biological activity of compound (6) was found to be comparable to that of the commercially available fungicides.